Transcallosal Removal of a Choroid Plexus Tumor From the Lateral Ventricle in a Dog. Case Report - Lehner, László; Czeibert, Kálmán; Benczik, Judit; Jakab, Csaba; Nagy, Gábor (Frontiers in Veterinary Science, 2020)
A 6-years-old female Staffordshire terrier was referred for periodic generalized seizures and asymmetric visual deficits. Magnetic resonance imaging revealed a 23.2 × 19.3 × 23.0 mm soft tissue mass within the right lateral ventricle and consequential dilatation of the lateral ventricles. Surgically, an interhemispheric approach was performed next to the marginal gyrus after a right parieto-parasagittal craniotomy, and a large choroid plexus tumor was transcallosally removed. After 3 days, the dog was discharged to home, and supportive treatment was continued. Histology revealed a choroid plexus papilloma, which was also confirmed by immunohistochemistry. One month after surgery, a control MRI showed that the ventricles were still dilated, but there was no sign of recurrent tumor. The dog had two additional seizures at home during the month following the intervention and one more grand mal episode was observed 4 months after the surgery. Nine months after the surgery, the dog showed no seizure activity, but her vision had not yet returned.